2022
DOI: 10.1111/cod.14028
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate‐containing consumer products in the US market

Abstract: Background Persulfate compounds are reactive oxidative agents increasingly recognized as contact allergens. Objectives The aim of this study was to identify common consumer products containing persulfate compounds in the US market. Methods Five publicly accessible online ingredient repositories and searches of two large online retailers were used to identify persulfate‐containing consumer products. Results We identified persulfates in 23 hair colouring products, 11 denture cleansers, 8 pool/hot‐tub products, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This is corroborated by data from the German Information Network of Departments of Dermatology (IVDK), showing that allergic contact dermatitis caused by ammonium persulfate is a health problem, especially in hairdressers, compared with clients or self‐users 20–22 . Accordingly, a current study from the United States concluded that clinicians should be aware of hair colouring products being one of the primary categories of consumer products that contain persulfate salts 23 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is corroborated by data from the German Information Network of Departments of Dermatology (IVDK), showing that allergic contact dermatitis caused by ammonium persulfate is a health problem, especially in hairdressers, compared with clients or self‐users 20–22 . Accordingly, a current study from the United States concluded that clinicians should be aware of hair colouring products being one of the primary categories of consumer products that contain persulfate salts 23 …”
Section: Discussionmentioning
confidence: 56%
“…[20][21][22] Accordingly, a current study from the United States concluded that clinicians should be aware of hair colouring products being one of the primary categories of consumer products that contain persulfate salts. 23 The market survey showed that most of the bleaching powders available on the German market are dust-free, which might lead to the idea that industry seems to have in part understood the problematic of bleach dusts in hairdressing. Also, the survey showed that the majority of hairdressers actually uses dust-free bleaching powders.…”
Section: Discussionmentioning
confidence: 99%